The Concept of Fiqh Ecotheology Integrated with Maqāṣid al-Sharī`at and Sustainable Development - Eny Latifah (Invest Journal of Sharia & Economic Law, 2026)
This study focuses on how the concept of ecotheology can be integrated into Maqāṣid al-Sharī`at and SDGs and how spiritual and environmental values can be integrated to achieve sustainable development. This research used a qualitative literature study. Data were obtained through document analysis, such as the concepts of fiqh ecotheology, maqāṣid al-sharī`at, and Sustainable Development Goals (SDGs) in published scientific articles from 2020 to 2025 and other references that can support the research objectives. This study shows that the concept of fiqh ecotheology that can be integrated with maqāṣid al-sharī`at and SDGs is environmental stewardship as a religious obligation, reflecting MQS1,3,5 and SDGs 14,15; prevention of environmental damage, reflecting MQS1,3,5 and SDGs 14,15; wise use of resources, interpreted through MQS1,3,5 and SDGs 13,14,15; sustainable development, illustrated in MQS1,3,5 and SDGs 11,14,15; ethical consumption, illustrated in MQS1,2,3,5 and SDGs 12,14; protection of animals and plants, reflecting the goals of MQS1,3,5 and SDGs 14; cooperation in environmental conservation, illustrated in the goals of MQS1,3,5 and SDGs 8,14; awareness and education, illustrated in the goals of MQS1,2,3 and SDGs 4,14. The application of the principle of maṣlaḥat through the instrument of Islamic philanthropy has similarities contained in the objectives of MQS1,4,5 and SDGs1,2,3,10; and the paradigm of “Ecological Tawḥīd” has integration with the objectives of MQS1,5 and SDGs 4,13,15. The spiritual values that exist in the fiqh of ecotheology in Maqāṣid al-Sharī`at and SDGs are balance (Mīzān), responsibility (Amānat), prohibition of destruction (Fasād fī al-'Arḍ), maintenance (Ḥifẓ), and sustainability (Istidāmat).